Infantile-onset Pompe disease (the first case diagnosed in Voronezh) - V. P. Fedotov; I. S. Kleimenova; T. V. Fedotova; D. S. Stepanov; E. A. Proskurina; E. Yu. Zakharova (Нервно-мышечные болезни, 2015)
Pompe disease (PD), or glycogen storage disease type II, is a rare autosomal recessive lysosomal disease caused by glycogen storage in the myocardium, skeletal muscles, and liver. PD, as an orphan disease with a very low prevalence rate, shows a marked clinical polymorphism, making its early diagnosis difficult. Yet, the efficiency of pathogenetic treatment for the disease is closely related to the time of its diagnosis, what is particularly relevant for infantile-onset PD. We present our clinical case of a sick baby with this condition diagnosed during life. The clinical diagnostic criteria were the neonatal form of rapidly progressive hypertrophic cardiomyopathy, macroglossia, floppy baby syndrome. Enzymatic diagnosis in the dried blood spots revealed the low activity of the enzyme α-glucosidase. Direct GAA gene sequencing identified heterozygous mutations in the infant’s parents: с.1799 G>A (p.Arg600His) in his father and c.1951_1952 delGGinsT in his mother, which allows its early prenatal diagnosis at 9-11 weeks of gestation.